Anatomic Characteristics, Identification, and Protection of the Nonrecurrent Laryngeal Nerve during Thyroidectomy. (August 2017) - Qiao, Na; Wu, Lin-feng; Gao, Wei; Qu, Feng-zhi; Duan, Peng-yu; Cao, Cheng-liang; Li, Pan-quan; Sun, Bei; Wang, Gang
Objective: We aimed to investigate the anatomical features and variation pattern of the nonrecurrent laryngeal nerve (NRLN), summarize the methods for identifying the NRLN before and during thyroidectomy, and share experiences regarding preventing and treating its injury. Study Design: Retrospective case data analysis. Setting: First Affiliated Hospital of Harbin Medical University. Subjects and Methods: Between January 2002 and May 2016, 7392 patients underwent thyroidectomy in our hospital. Of them, 28 patients with NRLN were identified, and their clinical data were retrospectively analyzed. Results: This study included 7392 patients in which the recurrent laryngeal nerves (RLNs) were routinely identified during surgery. The presence of NRLN was intraoperatively confirmed in 28 patients. All the NRLNs were located on the right side and its overall incidence was 0.37%. Five of the NRLNs were classified as type I, 19 as type IIa, and 4 as type IIb. Of the 28 cases, 4 NRLNs were injured during surgery, in which primary end-to-end anastomosis or local seal with corticosteroid injection was performed as a remedy. In the 4 patients with NRLN injury, 2 presented with postoperative hoarseness that indicated vocal cord paralysis confirmed by laryngoscope; the other 2 patients' voices had no significant changes. Conclusion: The NRLN, which is rare in clinical practice and predominantly right-sided, is anatomically more complex and variant at a higher risk of surgical injury. The key factors to accurately identify NRLN and to effectively prevent its injury include careful interpretation of auxiliary examination results before surgery, raising awareness of its presence, meticulous dissection, and routine exposure of the RLN during surgery.